40 years of JEEM: Research trends and influential publications in environmental and resource economics - Roland Kube; Andreas Löschel; Henrik Mertens; Till Requate (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2017)
This paper analyzes the way the content of the Journal of Environmental Economics and Management (JEEM) has developed over the last 40 years. We have classified the articles in the journal into five dimensions: content, methods, environmental media (pollutants and resources), cross-cutting issues and the regional dimension of studies. Up to about 10 years ago, non-market valuation and cost-benefit analysis, natural resource economics and environmental policy instruments were the subjects regularly representing the lion's share of the articles published in the journal. Thereafter we register a significant shift towards a more diversified array of research areas, with climate change and energy issues finding their way into the journal. In addition, increasing methodological plurality becomes apparent, reflected in a significant shift away from economic theory and towards empirical approaches. We also analyze key distinctions between the major environmental economics journals. To this end, we compare the 100 most frequently cited articles in JEEM, Ecological Economics, Land Economics, Environmental & Resource Economics, and the American Journal of Agricultural Economics. Here we find that non-market valuation studies play an important role in all the journals considered. Econometric studies are also widely represented in all of them, with theoretical models particularly strong in JEEM. Finally, we use citations as a criterion for analyzing JEEM's external influence on leading general economics (A+) journals. A regression analysis shows that a focus on market-based environmental policies and policy comparisons plus the use of econometric and statistical methods or experimental approaches correlates positively with an A+ citation. If we leave self-citations out of account, A+ citations are also positively correlated with a focus on air pollution and negatively correlated with a focus on water pollution and other pollutants.
Keywords: 330